Directions in Romanian Music of Banat Region in National and European Context - Demenescu, Veronica (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
The musicological studies on the compositional techniques approached by the representative composers from the Banat region, Romania and Europe reveal similarities in their creation. In this sense, we pointed out the main directions present in the Romanian music, as well as their connection to the European models, practiced between the end of the 19th century and the beginning of the 20th century. The connection of the Romanian creation to the European one of this period was made by the presence in the typologies of musical language of the common elements identified in the musical creation of the representatives of the national schools.